2011
DOI: 10.1007/s12230-011-9217-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Crossability in the Crosses between Solanum demissum and S. tuberosum, and the F1 and BC1 Progenies

Abstract: The Endosperm Balance Number (EBN) assigned to each species can foresee success or failure of a given interspecific cross in potatoes, although the underlying molecular basis is poorly studied. We found that the cross of Solanum demissum as female with a breeding line Saikai 35 constantly produced larger seeds (0.94 mg) than those from the reciprocal cross (0.39 mg), suggesting a slightly lower EBN in S. demissum. Crossing behaviors, measured by berry-setting rates, seeds/berry and seed size, in the reciprocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…However, the presence of germinating pollen grains came out for 49.3% of the samples, and for 35.2% of the samples, the percentage of germinating pollen grains scored more than 1%. These observations revealed compatibility with other researchers' data who also reported the sterile types of cytoplasm, also observing fertile pollens, which can be explained by nuclear-cytoplasmic interactions (Sanetomo et al, 2011, Gavrilenko et al, 2019.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…However, the presence of germinating pollen grains came out for 49.3% of the samples, and for 35.2% of the samples, the percentage of germinating pollen grains scored more than 1%. These observations revealed compatibility with other researchers' data who also reported the sterile types of cytoplasm, also observing fertile pollens, which can be explained by nuclear-cytoplasmic interactions (Sanetomo et al, 2011, Gavrilenko et al, 2019.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of occurrence of potato samples with tetrad sterility was approximately the same among the analyzed potato cultivars and breeding lines (15.3% and 15.8%, respectively). One believes that this type of sterility links with the W-type of cytoplasm, originating from the species S. stoloniferum, then used as a donor of resistance to potato Yvirus (Lössl et al, 2000;Song and Schwarzfischer, 2008;Sanetomo and Gebhardt, 2015). Such type of cytoplasm was also previously found among European cultivars (12.2%), cultivars bred in Russia and adjacent countries (8.7%), and Japanese potato collection (2.4%) (Sanetomo and Gebhardt, 2015;Gavrilenko et al, 2019;Hosaka and Sanetomo, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The Mexican hexaploid species, Solanum demissum is one of the tuber-bearing wild relatives to the cultivated potato, S. tuberosum and the most famous resource for the late blight disease caused by Phytophthora infestans (Ross 1986;Plastied and Hoopes 1989). Its EBN (Endosperm Balanced Number) value of four theoretically makes it directly crossable for breeding purposes with cultivated tetraploid potatoes (Hawkes 1990;Ortiz and Ehlenfeldt 1992;Cho et al 1997;Spooner et al 2014;Haynes and Qu 2016), and the species can easily be used to obtain hybrids with S. tuberosum (Dionne 1961;Sanetomo et al 2011). Moreover, it has been considered as an allohexaploid with three well-differentiated genomes (Ono et al 2016) and its nuclear genome composition has evolutionally been identified by a gene and GISH analysis (Spooner et al 2008;Pendinen et al 2012).…”
mentioning
confidence: 99%